Oxidative Modification in Human Hair: The Effect of the Levels of Cu (II) Ions, UV Exposure and Hair Pigmentation. (5th November 2015) - Grosvenor, Anita J.; Marsh, Jennifer; Thomas, Ancy; Vernon, James A.; Harland, Duane P.; Clerens, Stefan; Dyer, Jolon M.
Abstract: Protein oxidative degradation is implicated in a wide range of deleterious effects. For human hair, this oxidative damage can lead to significant observable changes in fiber physical and visual properties. A redox proteomic approach was applied to map molecular modification in human hair proteins and correlate this modification with the abundance of copper (II) ions, the levels of UV exposure and the general level of hair pigmentation. An increase in oxidative modification was observed with increasing copper (II) ion levels, regardless of the pigmentation level. Significantly, increased protein oxidative modification was also observed to occur in both lightly and darkly pigmented hair tresses even in the absence of irradiation, albeit at lower relative levels. Modification levels increased with increased copper (II) ion concentration. This new finding indicates that the level of copper (II) ions in human hair plays a key role in mediating protein oxidation, with or without exposure to UV light. Overall, these results strongly suggest that minimization of the level of copper (II) ions in human hair will mitigate and/or slow protein oxidative modification and therefore lower overall hair damage. Abstract : Human hair is exposed to a wide range of potentially modifying or damaging factors through daily routine, including sunlight and chemicals. This study describes molecular mapping of the effects of UV insult on the proteins of human hair, and how this modification varies with varying levels of copper (II) ions (introduced through washing) and differing levels of hair pigmentation. Advanced redox proteomic approaches were used to locate and track protein oxidation and correlate this modification to hair treatment.